2013
DOI: 10.1523/jneurosci.2989-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

FACS Array Profiling Identifies Ecto-5′ Nucleotidase as a Striatopallidal Neuron-Specific Gene Involved in Striatal-Dependent Learning

Abstract: The striatopallidal (STP) and striatonigral (STN) neurons constitute the main neuronal populations of the striatum. Despite the increasing knowledge concerning their involvement in multiple tasks associated with the striatum, it is still challenging to understand the precise differential functions of these two neuronal populations and to identify and study new genes involved in these functions. Here, we describe a reliable approach, applied on adult mouse brain, to generate specific STP and STN neuron gene pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 89 publications
3
36
0
Order By: Relevance
“…Our findings provide an explanation for the lack of the glycoprotein ecto-5′-nucleotidase (NT5e) staining reported earlier in the caudal part of the mouse striatum (Schoen and Graybiel, 1993). Indeed, NT5e, which hydrolyzes adenosine-5′ monophosphate to adenosine (Lee et al, 1986), has been recently found to be selectively expressed in D2R- and A2aR-expressing MSNs [see Table S2 in Heiman et al (2008); Ena et al (2013)].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings provide an explanation for the lack of the glycoprotein ecto-5′-nucleotidase (NT5e) staining reported earlier in the caudal part of the mouse striatum (Schoen and Graybiel, 1993). Indeed, NT5e, which hydrolyzes adenosine-5′ monophosphate to adenosine (Lee et al, 1986), has been recently found to be selectively expressed in D2R- and A2aR-expressing MSNs [see Table S2 in Heiman et al (2008); Ena et al (2013)].…”
Section: Discussionmentioning
confidence: 99%
“…The MrD exhibits some singular features including densely packed fusiform neurons (Shu et al, 1988) as well as high densities of immunoreactive terminals of a variety of neuropeptides including L-Enkephalin, substance P, neurotensin, somatostatin, cholecystokinin and dynorphin B (Shu et al, 1988, 1990, 1999). Interestingly, the best hallmark distinguishing the MrD from the other parts of the striatum is so far the lack of the striatopallidal-enriched protein, NT5e (Schoen and Graybiel, 1993; Ena et al, 2013). After a careful reviewing of the molecular markers defining the MrD, it is difficult to ascertain that the D2R/A2aR-expressing MSNs-poor zone of the caudal striatum and the MrD are one and the same subdivision.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed this cerebral region as some evidence points to the existence of striatal hyperdopaminergic activity secondary to hypofunction of the prefrontal dopamine system [32,33], whereas D 2 R and A 2A R are expressed mainly in medium-sized GABAergic spiny neurons [6]. Interestingly, a recent study showed that, in rodent, ecto-5′-nucleotidase is specifically expressed in this neuronal population, being responsible for most of the extracellular adenosine produced in the striatum [34]. Although the distribution of ecto-nucleotidases in the rodent brain has been deeply examined [22], little information was available on humans.…”
Section: Discussionmentioning
confidence: 99%
“…; Ena et al . ) and it was shown in lymphocytes that ecto‐5’‐nucleotidase and A 2A R undergo a coordinated induction (Napieralski et al . ).…”
Section: The Role Of A2ar In Neuroprotectionmentioning
confidence: 99%